Desenvolvimento de robô móvel e análise qualitativa de algorítmos de navegação fuzzy - Marin, Alexandre Jacques (2012)
This document presents a complete description of the reconstruction of a robotic platform, in addition to the development and test of two autonomous navigation algorithms for it, aiming to analyze and compare the behavior of the ED-FCM approach to robotic navigation (Event- Driven Fuzzy Cognitive Maps) against a classic Fuzzy logic based navigation. In this document, all steps of the reconstruction of the robotic platform, including all needed documentation for any future use, are described. Additionally, all theoretical knowledge necessary to understand both navigation algorithms is provided, together with all description of the implementation, test and comparison of the algorithms.